Femtoscopic correlations and the Lambda N-c interaction - Haidenbauer, J.; Krein, G. [UNESP]; Peixoto, T. C. [UNESP] (Springer, 2020)
We study the prospects for deducing constraints on the interaction of charmed baryons with nucleons from measurements of two-particle momentum correlation functions for Lambda(c)p. The correlation functions are calculated for Lambda(c)p and Sigma N-c interactions that have been extrapolated from lattice QCD simulations at unphysical masses of m(pi) = 410 - 570 MeV to the physical point using chiral effective field theory as guideline. In addition, we consider phenomenological YcN models from the literature to explore the sensitivity of the results to the properties of the interaction in detail. We find that a measurement of the Lambda(c)p correlation functions could indeed allow one to discriminate between strongly attractive Lambda N-c forces, as predicted by some phenomenological models, and a weakly attractive interaction as suggested by the presently available lattice simulations.